Preliminary Synthesis of Calcium Silicates using Oil Palm Leaves and Eggshells. - Salprima Yudha S; Aswin Falahudin; Noor Haida Mohd Kaus; Sirikanjana Thongmee; Saiqa Ikram; Asdim Asdim (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
A new synthetic procedure is described for the synthesis of calcium silicate derivatives, using natural resources such as eggshell (ES) for calcium and oil palm leaves (OPL) for silica, which do not require prepurification. The reaction is performed by directly converting two weight ratio of the precursors, ES:3OPL and ES:6OPL, to dried-powder form by heat treatment at 900 °C for two hours. The results demonstrate that the concentration of the precursors has an effect on the morphology and crystallinity of the calcium silicate derivatives, mainly Ca2SiO4 and CaSiO3. X-ray diffraction results reveal that the reaction product obtained using a 1:3 ratio is quite pure, and mainly consisted of calcium silicate in the form of Ca2SiO4. The CaSiO3 was also identified in ES:6OPL, together with a small amount of excess non-reacted crystalline silica. Furthermore, a scanning electron microscopy analysis shows that both reaction products have a coarse surface. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).